Impact of Digital Payment on Economic Growth: Evidence from Indonesia - Dian Putri Maharani; Naziha Romiza; Syauqi Irfan; Ratu Eva Febriani (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
Innovations in the payment system that lead to non-cash payments (digital payment) can potentially impact output, prices, and monetary policy transmission that will be driving the economy faster. However, in its work, there is a conspicuous lack of the role of digital payments in encouraging economic activity, especially for an emerging economy like Indonesia. This research is aimed to evaluate the impact of digital payment on economic growth but also look at the influence of government spending and inflation as control variables on economic growth. In reviewing this empirical concept, a quantitative analysis is applied to assess the research construct by using a panel regression approach. The data used are sourced from Bank Indonesia and the Central Bureau of Statistics for the observation period from 2018 to 2021. Findings revealed the significance of each variable that represents a positive impact of digital payments and inflation on economic growth, while government spending harms economic growth.